2019
DOI: 10.1093/toxsci/kfz215
|View full text |Cite
|
Sign up to set email alerts
|

Acute 4,4′-Methylene Diphenyl Diisocyanate Exposure-Mediated Downregulation of miR-206-3p and miR-381-3p Activates Inducible Nitric Oxide Synthase Transcription by Targeting Calcineurin/NFAT Signaling in Macrophages

Abstract: Exposure to 4,4′-methylene diphenyl diisocyanate (MDI) in the occupational setting may lead to development of occupational asthma (OA), and the underlying molecular mechanisms of MDI-induced disease pathogenesis remain an active area of research. Using a nose-only mouse inhalation model, we find that circulating microRNA (miR)-206–3p and miR-381–3p are downregulated after MDI exposure; however, cellular miR-206–3p and miR-381–3p responses after MDI aerosol exposure and their pathophysiological roles in MDI-OA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 97 publications
2
8
0
Order By: Relevance
“…Our findings are consistent with the report that miR-206 expression was decreased in airway wall of a mouse model of childhood allergic asthma [57]. Recent studies showed that miR-206 expression was also decreased in mouse models of occupational asthma [58, 59]. In human, it was reported that circulating miR-206 was useful to predict childhood asthma exacerbation [60], and plasma miR-206 expression differed between asthmatics with higher and lower blood eosinophil counts [61].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with the report that miR-206 expression was decreased in airway wall of a mouse model of childhood allergic asthma [57]. Recent studies showed that miR-206 expression was also decreased in mouse models of occupational asthma [58, 59]. In human, it was reported that circulating miR-206 was useful to predict childhood asthma exacerbation [60], and plasma miR-206 expression differed between asthmatics with higher and lower blood eosinophil counts [61].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, studies on hsa-mir-206 have become a hot topic, but studies on AML are still lacking. Notably, we found that a recent study by Chen et al [25] on occupational asthma (OA) proposed a regulatory axis similar to that in this study. They pointed out that miR-206-3p, as a key factor in calcineurin/NFAT signaling in macrophages and bronchoalveolar lavage cells, affects the transcription of iNOS and thus regulates the development of OA.…”
Section: Discussionsupporting
confidence: 88%
“…miRNA can regulate arginine metabolism by regulating the expression of key molecules in arginine metabolism pathway, such as ASS ( Bates et al, 2010 ; Tu et al, 2020 ), ARG1 ( Bates et al, 2010 ; Yoo et al, 2019 ), ARG2 ( Dunand-Sauthier et al, 2014 ; Jin et al, 2014 ; Kim et al, 2017 ; Wang Y. et al, 2017 ), CAT-1 ( Chang et al, 2004 ; Li Y. et al, 2018 ), ODC ( Jagannathan et al, 2015 ) and NOS ( Perske et al, 2010 ; Yan et al, 2011 ; Guo et al, 2012 ; Sun et al, 2012 ; Zhu et al, 2013 ; Li et al, 2014 , 2017 , Li H.T. et al, 2018 ; Fu et al, 2015 ; Jiang et al, 2015 ; Zhang et al, 2015 , 2020 ; Rasheed et al, 2016 ; Reilly et al, 2016 ; Muxel et al, 2017 , 2018 ; Wang C. et al, 2017 , Wang et al, 2019 ; Cui et al, 2020 ; Lin et al, 2020 ; Scalavino et al, 2020 ; Table 1 ). It has been found that multiple miRNAs could target the same enzyme or transporter protein, and the same molecule could also be regulated by multiple miRNAs.…”
Section: Mirnas and Long Non-coding Rnas In Arginine Metabolism And Crcmentioning
confidence: 99%